High-throughput sequencing for plant virology diagnostics and its potential in plant health certification - Maina, Solomon; Donovan, Nerida J.; Plett, Krista; Bogema, Daniel; Rodoni, Brendan C. (Frontiers in Horticulture, 2024)
Abstract: High-throughput sequencing (HTS) technologies have revolutionized plant virology through simultaneous detection of mixed viral infections. Recent HTS advances have uncovered and improved understanding of virus biology, ecology, and evolution which is vital for viral disease management. Plant viruses continue to threaten global agricultural productivity and strict quarantine measures are essential to prevent the introduction and spread of virulent viruses around the world. The gradual decrease in HTS operational costs, including improved computational systems and automation through robotics, has facilitated the adoption of this tool for plant diagnostics, including its use in surveillance and quarantine programs. . However, the speed of technology advancements and distinct HTS chemistries, laboratory procedures, data management and bioinformatic analyses have proven challenging. In addition, the lack of viral species reference sequences, compared with the estimated number of distinct viral taxa, makes classification and identification of novel viruses difficult. There is a need for standardized HTS testing, especially within plant health programs. In this review, we consider the application of HTS in plant virology, explore the technical challenges faced and the opportunities for HTS in plant health certification. We propose standards for overcoming current barriers and for ensuring reliable and reproducible results. These efforts will impact global plant health by reducing the risk of introduction and the spread of damaging novel viruses.